Economic Analysis of Automatic Meter Reading on Web Based in Türkiye Using Nginx Load Balancer Technology - Karaaslan, Şükrü; Kayaoğlu, Mazhar; Gedikpinar, Mehmet; Sengur, Abdulkadir (My University, 2024)
Electricity meters, which are read manually, bring a great financial burden to companies in terms of workload, time and economy. In this study, examined the reading of electric meters automatically process, Turkey focused on cost-benefit analysis performed. With the ever-increasing electricity consumption, the number of electricity expenses and accordingly the number of subscribers increases. Along with the increasing number of electricity consumers, the number of subscribers and consequently electricity consumption increases. Automatic Meter Reading Systems is one of the recommended solution packages for Energy Management Systems. It is for python programming language and its frameworks as software infrastructure. Nginx is used as a web server, and Web Server Gateway Interface and Gunicorn frameworks are used for the connection between the application and the web server. Thanks to automatic meter reading system, which has an extremely fast reading structure, it is predicted that tens of thousands of electricity meters can be read over the internet in seconds. Nginx Load Balancer software technology is capable of transferring tens of thousands of indexes to the database at once. This technology is able to distribute data load and respond to data traffic. In addition, the effect of reading cost on Energy Management Systems is analyzed in meters that are read manually. Turkey's Elazig province, economic research analysis was conducted on a total of 334 thousand electricity subscribers. According to survey data, 47 million has electricity subscribers in Turkey. In addition, cost-benefit analysis of the meters that are foreseen to be read in Nginx load balancer software technology is performed.
Keywords: Automatic meter reading; Techno economic analysis; Load balancer